The The Role of the ASEAN Prosecutors/Attorneys General Forum in Strengthening Cooperation in Prosecuting Transnational Crimes - _septianingrum12, vina_ayu (The Prosecutor Law Review, 2026)
Globalization has increased the intensity of transnational crimes involving more than one jurisdiction and poses serious challenges to national law enforcement systems. As a region with high mobility of people, goods, and capital, Southeast Asia is vulnerable to various forms of transnational crime, such as human trafficking, narcotics, money laundering, and cybercrime. This situation demands more effective coordination between prosecutorial institutions at the regional level. This study aims to analyze the role of the ASEAN Prosecutors/Attorneys General forum in strengthening cooperation in the prosecution of transnational crimes in the Southeast Asian region. The research method used is normative juridical with a legislative and conceptual approach. The results show that the APAG forum, which was inaugurated through the Sanur Bali Declaration 2025, is positioned as a sectoral ministerial body under the ASEAN Political and Security Community Council. The forum's strategic role includes its function as a forum for coordinating cross-jurisdictional prosecutions, facilitator of harmonizing understanding of MLA procedures, capacity building for prosecutors, and driving harmonization of criminal norms through soft law instruments. The presence of the APAG forum has proven crucial and effective in bridging differences in legal systems and reducing diplomatic bureaucracy without interfering with the sovereignty of each member state, in line with the ideals of the ASEAN Community Vision 2045.